Bonus Taxes and International Competition for Bank Managers - Daniel Gietl; Andreas Haufler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the competition in bonus taxation when banks compensate their managers by means of incentive pay and bankers are internationally mobile. Bonus taxes make incentive pay more costly for national banks and lead to an outflow of managers, lower effort and less risk-taking in equilibrium. The international competition in bonus taxes may feature a `race to the bottom', or a `race to the top', depending on whether bankers exert a positive or a negative fiscal value on their home government. The latter can arise when governments bail out banks in the case of default, and bankers take excessive risks as a result of incentive pay.
Keywords: H20; H87; G28; 330